A reconstruction of the stratigraphic position of a former Middle Palaeolithic surface site at Rotselaar – Toren ter Heide (Flemish Valley, Belgium) using mechanical sounding and geochemical fingerprinting. (December 2017) - Van Peer, Philip; Willems, Mark; Degryse, Patrick; Claeys, Philippe; Marinova, Elena
Highlights: We have used mechanical sounding for a stratigraphic study of the site locale. We have identified the Lower Valley Fill as the likely window of human occupation. We found matching geochemical compositions of sediments and accretions on lithics. The probable chronostratigraphic position of the Rotselaar site is final Eemian.